Capital mobility, exchange rates, and economic crises - Fane, George (Cheltenham, UK ; Northampton, MA, USA : E. Elgar Pub., 2000)
Recent crises in emerging markets have raised doubts about relaxing controls on capital mobility. This book uses evidence from the crises in Asia and Latin America to reassert the traditional case that such controls are an excessively blunt instrument for achieving financial stability.
Includes bibliographical references (p. 199-209) and index.
oif 11/07/2016
Loans
Keywords: Capital movements; Foreign exchange; Financial crises; Currency question